Influence of Standard Operational Procedures on Employee Performance in Technical Preparation for Public Order and Community Tranquility at the Regional Civil Service Police Unit of North Nias District - Nazara, Sanaria; Hulu, Perlindungan Faebuadodo; Mendrofa, Yupiter; Telaumbanua, Aferiaman (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
The aim of the research is to find out how to understand the formulation of the problem above. To realize this goal, data collection techniques are carried out by means of distributing questionnaires, observation and documentation. This thesis uses a type of quantitative research based on questionnaires in processing data, so that the data obtained is more accurate. The results of this research are a) From the results of the validity test, it was found that each question item used in the questionnaire was declared valid. Where the value obtained from the results of data analysis is the calculated r value > the rt table value. The results of the reliability test show that the Croanbachalpha value for each variable has a Croanbach alpha value > 0.60. So it can be concluded that the measuring instrument used is a reliable measuring instrument. The results of the simple linear regression test showed that the significance level was 0.000 < 0.05. Which indicates that standard operational procedures can influence Employee Performance in Technical Operational Preparation for Public Order and Community Peace in the Civil Service Police Unit of North Nias Regency. From the results of the T test calculations it was found that t count > t table or 7.515 > 1.697, it can be concluded that the hypothesis is accepted is ha where there is an influence of standard operational procedures on Employee Performance in Technical Operational Preparation for Public Order and Community Peace in the Civil Service Police Unit of North Nias Regency. Standard operating procedures support or influence Employee Performance in Technical Operational Preparation for Public Order and Community Peace in the North Nias Regency Civil Service Police Unit with an influence of 71.1% while the remaining 28.9% is influenced by other factors that are not involved. examined in this research. The value obtained from the results of the correlation test between standard operational procedure variables and employee performance is 0.743, which is at a strong relationship level.